I Implementasi Chatbot Berbasis Telegram Untuk Manajemen Konfigurasi Dan Notifikasi Intrusion Prevention System (IPS) Suricata - irawan, nanang (Universitas Multi Data Palembang, 2025)
This study aims to develop and implement a Telegram-based chatbot system integrated with the Suricata Intrusion Prevention System (IPS) to support real-time network security configuration management and notifications. The system is capable of detecting attacks such as Brute Force and DDoS, and delivers instant notifications to administrators via Telegram, with an average delivery time of less than 2 seconds. The chatbot enables administrators to remotely execute various configuration commands, such as monitoring Suricata status, managing rules, blocking IP addresses, and tracking system resource usage, with response times ranging from 4 to 7 seconds. Testing in a virtual environment demonstrates that the system operates stably and efficiently, even under active attack conditions. The Network Development Life Cycle (NDLC) method was employed in the development process and proved effective in designing the system's workflow and functionalities. The results of this study indicate that integrating a chatbot with an IPS via the Telegram platform offers a practical, fast, and centralized solution for monitoring and managing network security.